Guanidino-Acetic Acid: A Scarce Substance in Biomass That Can Regulate Postmortem Meat Glycolysis of Broilers Subjected to Pre-slaughter Transportation - Zhang, Bolin; Liu, Ning; He, Zhen; Song, Peiyong; Hao, Meilin; Xie, Yuxiao; Li, Jiahui; Liu, Rujie; Sun, Zewei (Frontiers in Bioengineering and Biotechnology, 2021)
The different substances in biomass can regulate the metabolism and reproduction of broilers. Guanidino-acetic acid (GAA) is the natural feed additive that showed a potential application in dietary for broilers, while its amount is scarce in biomass. The objective of the present study was to investigate the effects of dietary supplemented with GAA on muscle glycolysis of broilers subjected to pre-slaughter transportation. A total of 160 Qiandongnan Xiaoxiang Chicken were randomly assigned into three treatments, including a basal control diet without GAA supplementation (80 birds), or supplemented with 600 mg/kg (40 birds) or 1,200 mg/kg (40 birds) GAA for 14 days. At the end of the experiment, the control group was equally divided into two groups, thus resulted in four groups. All birds in four groups aforementioned were separately treated according to the following protocols: 1) no transport of birds of control group fed with the basal diet; 2) a 3 h transport of birds of control group fed with the basal diet; 3) a 3 h transport of birds fed with diets supplemented with 600 mg/kg GAA; 4) a 3 h transport of birds fed with diets supplemented with 1 200 mg/kg GAA. The results demonstrated that 3h pre-slaughter transport increased corticosterone contents and lowered glucose contents in plasma (P<0.05), decreased pH24h (P<0.05), and resulted in inferior meat quality evidenced by elevating the drip loss, cooking loss and L* value (P<0.05). Meanwhile, 3h pre-slaughter transport decreased the contents of Cr and ATP in muscle (P<0.05), elevated the ratio of AMP : ATP and glycolytic potential (P<0.05). Moreover, 3h pre-slaughter transport resulted in a significant elevation of mRNA expressions of LKB1 and AMPKα2 (P<0.05), as well as the increased of protein abundances of LKB1 phosphorylation and AMPKα phosphorylation (P<0.05). However, 1200 mg/kg GAA supplementation alleviated negative parameters in plasma, improved meat quality, ameliorated postmortem glycolysis and energy metabolism through regulating the creatine-phosphocreatine cycle and key factors of AMPK signaling. In conclusion, dietary supplementation with 1200 mg/kg GAA contributed to improving meat quality via ameliorating muscle energy expenditure and delaying anaerobic glycolysis of broilers subjected to 3 h pre-slaughter transport.